Incidence of solid cancers among residents near nuclear facilities: a systematic review and meta-analysis - Ga Bin Lee; Yerin Hwang; Soojin Park; Eun-Shil Cha; Dalnim Lee; Kyungsik Kim; Sue K. Park; Minsu Cho; Songwon Seo (BMC Public Health)
Abstract Background Concerns about the potential health effects of radiation exposure in communities living near nuclear facilities persist, prompting ongoing studies across various countries. However, research on solid cancers in these communities remains limited. This systematic review and meta-analysis aimed to comprehensively investigate the incidence of various solid cancers among residents near nuclear facilities, providing up-to-date scientific evidence on potential health effects in the context of energy security and net-zero emission targets. Methods A comprehensive search of the databases PubMed, Excerpta Medica Database, and Web of Science was conducted. Data were extracted from 13 studies on breast, bladder, thyroid, CNS, and respiratory cancers, with the meta-analysis focusing on cancer types supported by at least five quantitative estimates to account for study heterogeneity. Study quality was assessed using the Office of Health Assessment and Translation tool. Pooled standardized incidence ratios (SIRs) were calculated using random-effects models, and publication bias was evaluated using funnel plots and Egger’s test. Results The meta-analyses included the following number of cases for each selected cancer type: breast, n = 20,701; bladder, n = 5,398; thyroid, n = 9,907; CNS, n = 3,634; and respiratory system, n = 18,033. Pooled SIRs for all cancer subtypes were statistically insignificant and ranged from 0.99 to 1.04, with substantial heterogeneity among studies (I 2 range: 64%–96%). Little evidence of publication bias was revealed upon visual inspection of the funnel plots and performing Egger’s test. Conclusions Current scientific evidence regarding the incidence of solid cancers in populations living near nuclear facilities is insufficient to draw definitive conclusions. Nonetheless, the wide range of heterogeneity among studies highlights the need for further research with refined study designs, particularly with regard to radiation exposure and individual-level confounding factors, to provide more robust evidence on the public health implications for residents near nuclear facilities.